Digital Innovations in Petanque Sport: A Study on the Perceived Benefits and Barriers of Using an Android-Based Application - Muchamad Arif Al Ardha; Kolektus Oky Ristanto; Rizky Muhammad Sidik; Muhammad Kharis Fajar; Advendi Kristiyandaru; Sauqi Sawa Bikalawan; Oce Wiriawan; Kukuh Pambuka Putra (International Journal of Computer Technology and Science, 2025)
The rapid evolution of digital technology has significantly impacted various sports, including niche ones like petanque. This study explores the perceived benefits and barriers of using an Android-based application for scoring and statistics management in petanque, a sport gaining popularity in Indonesia. Traditionally, performance assessment in petanque relied on manual, paper-based methods, prone to inaccuracies and inefficiencies. An Android app, Petanque Match Statistics, was developed to address these challenges, offering real-time data accuracy, improved workflow, and enhanced performance analysis. This study employed a quantitative approach, surveying 50 participants (35 players and 15 coaches) in Surabaya, Indonesia, to assess their impressions of the app's usability, accuracy, efficiency, and overall satisfaction. Results indicated high ratings across all parameters, with no significant differences between players and coaches. The app was commended for its intuitive design, reliability, and time-saving efficiency. Findings highlight the potential of digital solutions to modernise petanque match administration, enhance strategic decision-making, and improve the user experience. The study underscores the importance of user-centred design in facilitating the adoption of digital advancements in sports, offering valuable insights for future developments in petanque and other emerging sports.